Persistence of health inequalities in childhood injury in the UK: a population-based cohort study of children under 5 - Orton, Elizabeth; Kendrick, Denise; West, Joe; Tata, Laila J. (Public Library of Science, 2014)
BACKGROUND: Injury is a significant cause of childhood death and can result in substantial long-term disability. Injuries are more common in children from socio-economically deprived families, contributing to health inequalities between the most and least affluent. However, little is known about how the relationship between injuries and deprivation has changed over time in the UK.